Regulation and Culture Change in the Process of Europeanisation in Neighbor Economies: The Case of Competition Regulation in Moldova - Theodore KOUTSOBINAS; Rodica CRUDU (Eastern European Journal of Regional Studies)
International economic relations are increasingly governed by trade agreements that give rise to regional associations. In this context, main socio-economic paradigms expand and, as a result, processes such as Europeanisation in the case of European Union emerge. A key foundation of Europeanisation is the adoption of regulation according to EU acquis by ascending member and partner countries. Besides the prospects of massive adoption of regulation and application of related enforcement, an important mechanism for paradigm expansion is the implementation of culture change in the regulation framework. The paper discusses Europeanisation in the light of the theory of institutional culture change as a planning and public policy instrument. The impact of institutional cultural change is examined in the context of regulation, by using as a special case the competition framework. The advantages and difficulties of promoting competition culture are discussed in an international context and with regard to transition economies subject to Europeanisation, taking developments in Moldova as a case-study. The main finding is that culture change implementation must be incorporated into the strategic planning of regulatory authorities to mitigate the risk of possible policy erosion or bottlenecks.